Complementary and alternative medicine therapies for uremic pruritus – A systematic review of randomized controlled trials. (January 2021) - Yeam, Cheng Teng; Yo, Tiffany Eri; Tan, Ying Lin Cheryl; Liew, Adrian; Seng, Jun Jie Benjamin
Highlights: Acupuncture, acupressure and topical capsaicin were effective for uremic pruritus. Omega-3 fatty acids and zinc showed mixed efficacy in treating uremic pruritus. Larger trials are needed to evaluate efficacy of complementary alternative medicine. Abstract: Introduction: Uremic pruritus (UP) is one of the most bothersome symptoms among chronic kidney disease (CKD) patients. The pathophysiology of UP remains elusive, resulting in limited treatment options. The inability of standard medical treatments to provide effective relief has piqued interest in complementary and alternative medicine (CAM). Methodology: A systematic review of randomized controlled trials (RCTs) summarizing the efficacy and safety profile of CAM used for UP in CKD patients was performed. CAM interventions were classified using categories proposed by the National Center for Complementary and Integrative Health. The efficacy of each CAM was determined from changes in UP severity and all reported adverse effects were extracted. Results: Of 5242 articles screened, 34 RCTs were included, with 15 (44.1 %) studies having a sample size greater than 50. The studies considered 21 treatments including omega-3 fatty acid supplementation (n=5), acupuncture (n=5), topical capsaicin (n=4) and acupressure (n=3). Acupuncture, acupressure and topical capsaicin were shown to be effective in improving uremic pruritus. Interventions which include oral omega-3 fatty acid and zinc supplementation demonstrated mixed efficacy. Other therapies such as evening primrose oil, turmeric, vitamin B3, vitamin D and thermal therapy were not effective for treatment of UP. Common adverse effects reported with topical capsaicin included mild burning sensations (50.0–88.2 %) or erythema (6.7–22.7%) while that of acupuncture included soreness (7.5 %), bleeding (6.0–7.5%) and hematoma (1.9 %). Conclusions: Acupuncture, acupressure and topical capsaicin have the largest body of evidence for efficacy in the treatment of UP. Larger and higher quality RCTs are required to examine the efficacy and safety of promising CAM.